Using antioppressive teaching principles to transform a graduate global health course at Johns Hopkins University. Issue 3 (28th March 2023) - Kalbarczyk, Anna; Aqil, Anushka; Sauer, Molly; Chatterjee, Pranab; Jacques, Keilah A; Mooney, Graham; Labrique, Alain; Lee, Krystal
Abstract : Education systems and pedagogical practices in global public health are facing substantive calls for change during the current and ongoing 'decolonising global health' movement. Incorporating antioppressive principles into learning communities is one promising approach to decolonising global health education. We sought to transform a four-credit graduate-level global health course at the Johns Hopkins Bloomberg School of Public Health using antioppressive principles. One member of the teaching team attended a year-long training designed to support changes in pedagogical philosophy, syllabus development, course design, course implementation, assignments, grading, and student engagement. We incorporated regular student self-reflections designed to capture student experiences and elicit constant feedback to inform real-time changes responsive to student needs. Our efforts at remediating the emerging limitations of one course in graduate global health education provide an example of overhauling graduate education to remain relevant in a rapidly changing global order.